2016
DOI: 10.1073/pnas.1601918113
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of β-catenin activity by BIG1 plus BIG2 via Arf activation and cAMP signals

Abstract: Multifunctional β-catenin, with critical roles in both cell-cell adhesion and Wnt-signaling pathways, was among HeLa cell proteins coimmunoprecipitated by antibodies against brefeldin A-inhibited guanine nucleotide-exchange factors 1 and 2 (BIG1 or BIG2) that activate ADP-ribosylation factors (Arfs) by accelerating the replacement of bound GDP with GTP. BIG proteins also contain A-kinase anchoring protein (AKAP) sequences that can act as scaffolds for multimolecular assemblies that facilitate and limit cAMP si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 69 publications
(109 reference statements)
2
12
0
Order By: Relevance
“…In addition, activation of PI3K/ Akt also induces VEGF expression in ECs (53,54). Consistent with previous findings in HeLa cells (28) and thyroid cancer (52), knockdown of BIG1 and BIG2 in HUVECs significantly reduces phosphorylation of Akt. Although it is still not clear how BIG1 and BIG2 interfere with phosphorylation of Akt, we show here that incubation with SC79, which specifically enhances Akt phosphorylation, can rescue the suppression of VEGF expression after BIG1 or BIG2 knockdown in HUVECs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, activation of PI3K/ Akt also induces VEGF expression in ECs (53,54). Consistent with previous findings in HeLa cells (28) and thyroid cancer (52), knockdown of BIG1 and BIG2 in HUVECs significantly reduces phosphorylation of Akt. Although it is still not clear how BIG1 and BIG2 interfere with phosphorylation of Akt, we show here that incubation with SC79, which specifically enhances Akt phosphorylation, can rescue the suppression of VEGF expression after BIG1 or BIG2 knockdown in HUVECs.…”
Section: Discussionsupporting
confidence: 91%
“…In previous reports, depletion of BIG1 or BIG2 in HeLa cells decreased phosphorylation of Akt at S473 (28), and knockdown of BIG1 in papillary thyroid cancer cells also inhibited Akt signaling to attenuate epithelialmesenchymal transition and reduce cell migration and invasion (52). Because PI3K-Akt signaling is known to mediate VEGF expression in ECs (53,54), we next examined the effects of BIG1 or BIG2 knockdown on activation of Akt in HUVECs.…”
Section: Up-regulation Of Vegf Signaling Rescues Angiogenic Isv Growtmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, Li et al found that BIG1 physically interacted with β‐catenin, and that knockdown of BIG1 or BIG2 tethered β‐catenin at perinuclear Golgi structures without changing β‐catenin expression. These results imply that the accumulation of β‐catenin at Golgi structures after inhibition of BIG1 or BIG2 might contribute to the suppression of Wnt signaling by delaying β‐catenin transit to the nuclei (Li, Le, Kato, Moss, & Vaughan, ). We found that BFA decreased β‐catenin transcripts (Figure d); therefore, these Golgi disruptors might not only suppress the transcription of β‐catenin, but also alter its distribution in cells.…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin is a key component of Wnt signaling pathway and active β-catenin is found in diverse kidney diseases including focal segmental glomerulosclerosis (FSGS) and DN 19 , 30 . Excess cytoplasmic β-catenin is often targeted by a N-terminal phosphorylation/ubiquitylation-mediated degradation system 31 35 . N-terminus dephosphorylation of β-catenin is sufficient to induce stabilized β-catenin migrating into the nucleus 10 , 28 .…”
Section: Discussionmentioning
confidence: 99%